1970
DOI: 10.1246/bcsj.43.81
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl Bromide-Amine Reaction in Nitrobenzene-Ethanol Mixtures

Abstract: The reactions between benzyl bromide and various bases as well as p-nitrobenzyl bromide and various bases have been studied in nitrobenzene-ethanol mixtures (80:20 v/v). The reaction is total second order as stated earlier. Comparison is made with the previous work on the same reaction with benzyl chloride and p-nitrobenzyl chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Nucleophilic substitution at the benzylic carbon is of broad synthetic utility and has received considerable attention from organic chemists. Literature survey shows that applications of the Hammett equation on different nucleophilic substitution reactions involving nucleophiles, namely thiourea , thiobenzamide , pyridines , quinolines , different aliphatic and aromatic primary and secondary amines , and 2‐mercapto benzimidazole have been reported. In continuation of our earlier work on the benzylation of N‐substituted benzylamines with benzyl bromide , we are reporting herein the effect of substituents attached to the benzene ring of benzylamine on the reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleophilic substitution at the benzylic carbon is of broad synthetic utility and has received considerable attention from organic chemists. Literature survey shows that applications of the Hammett equation on different nucleophilic substitution reactions involving nucleophiles, namely thiourea , thiobenzamide , pyridines , quinolines , different aliphatic and aromatic primary and secondary amines , and 2‐mercapto benzimidazole have been reported. In continuation of our earlier work on the benzylation of N‐substituted benzylamines with benzyl bromide , we are reporting herein the effect of substituents attached to the benzene ring of benzylamine on the reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental concepts like steric effects, nucleophilicity, solvent effects and structure reactivity correlations have been developed. Literature survey shows that a variety of nucleophiles, namely thiourea, 1 thiobenzamide, 2 pyridines, 3 quinolines 3 , different aliphatic and aromatic primary and secondary amines, 4 2mercapto benzimidazole 5 and 2-mercaptobenzoxazole, 6 have been used in these studies. As part of our broad programme on the benzylation of secondary amines hither to not reported in the literature, we studied the effect of solvents, 7 on the benzylation of diphenyl amine using benzyl bromide.…”
Section: Introductionmentioning
confidence: 99%
“…48 Also, in 1968, Radhakrishnamurti and Panigrahi showed that benzyl bromides react faster than benzyl chlorides in an S N 2 type, solution based reaction. 49 Similarly, given more time and energy in the high speed ball mill, benzyl chloride reacts to give a 62% yield in 17 h. Although much less reactive, Cl can be used as a leaving group in S N 2 type reactions using high speed ball milling. Also less reactive, (2bromoethyl)benzene gives only a 5% conversion to the dialkyl carbonate product in 2 h but jumps to 58% conversion after 17 h. We attribute this to less cationic character in the carbon next to the bromine in (2-bromoethyl)benzene when compared to the carbon next to the bromine in benzyl bromide.…”
mentioning
confidence: 99%